Magnetovariational method and result of testing models - Van, Nguyen Thanh (Vietnam Journal of Earth Sciences, 2012)
Many scientific projects relevant to five elements of electromagnetic field show that Magnetotelluric (MT) method can be applied in researching inhomogeneity of 2D and 3D models. Therefore, simultaneous analysis of these magnetotelluric elements recorded in distant station such as (Ex, Ey, Hx, Hy, and Hz) is concerned in the MT method. When frequencies of electromagnetic field changes, the field’s elements are related through relational tensors which were impedance tensors (Zij) and pulse transfer function (Wij). More scientific research is interested in data analysis, especially applying data measurements of distant stations in noise filtering. Nowadays, one of the effective methods to study the geoelectrical inhomogeneity is the variable magnetic section, in which relations between the variable components Hx, Hy, Hz of the geomagnetic field are given by Wiese - Parkinson matrix. There are many models of transforming and representing this matrix to obtain useful information such as magnetic polarisation diagram, induction vector, magnetovariational vector, magnetovariational phase and ellipticity. The paper present the application of using above magnetovariational parameters to study the geoelectrical inhomogeneities on models and practical application.